1992
DOI: 10.1002/jbm.820261202
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility of human whole blood on polymers with a phospholipid polar group and its mechanism

Abstract: The hemocompatibility of a polymer containing a phospholipid polar group, poly(2-methacryloyloxyethyl phosphorylcholine (MPC)-co-n-butyl methacrylate(BMA)), with human whole blood was evaluated. When human whole blood without an anticoagulant was contacted with polymers, the blood cell adhesion and aggregation on the polymer without the MPC moiety was extensive, and considerable fibrin deposition was observed. This phenomenon was suppressed with an increase in the polymer MPC composition. Thus, the MPC moiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
296
1
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 437 publications
(308 citation statements)
references
References 10 publications
8
296
1
3
Order By: Relevance
“…15,16) The PMPC brush has also attracted a great deal of interest because of its excellent biocompatibility 17,18) and its antifouling behavior. 19) In order to understand the mechanism of such excellent biocompatibility and the lubrication behavior, it is very important to examine the swollen structure, the conformation of polyelectrolyte brushes in an aqueous solution, and the dependence on ionic strength in comparison to the solution properties of unbound, free polyelectrolytes.…”
Section: Chain Dimension Of Polyelectrolyte In Solution and Immobilizmentioning
confidence: 99%
“…15,16) The PMPC brush has also attracted a great deal of interest because of its excellent biocompatibility 17,18) and its antifouling behavior. 19) In order to understand the mechanism of such excellent biocompatibility and the lubrication behavior, it is very important to examine the swollen structure, the conformation of polyelectrolyte brushes in an aqueous solution, and the dependence on ionic strength in comparison to the solution properties of unbound, free polyelectrolytes.…”
Section: Chain Dimension Of Polyelectrolyte In Solution and Immobilizmentioning
confidence: 99%
“…The expectation of protein resistance is based on the hypothesis that these groups should mimic the lipid component of the cell surface (10) which is supposed to be essentially protein resistant. Ishihara et al (11) have suggested that arrays of such PC moieties attached to a surface in contact with blood will bind phospholipids and organize them into structures that are lipid bilayer-like, and thus protein resistant. The paper by Nakabayashi et al in this volume provides additional data in support of this concept.…”
Section: Theory and Molecular Mechanisms Of Protein Adsorptionmentioning
confidence: 99%
“…Research in the development of enzyme electrodes for biofuel cell and biosensor applications has been carried out extensively in recent years. Studies on understanding the reaction mechanisms of enzyme catalytic reactions [14,15], developing new biomaterials [16][17][18][19][20], on enzyme modification [21][22][23][24][25][26][27], enzyme immobilisation methods [28][29][30][31][32][33][34], and enzyme electrode structures [35] have been reported in the literature in an effort to improve the performance of enzyme electrodes.…”
Section: Open Accessmentioning
confidence: 99%
“…Biopolymers based on phospholipid polymer mimicking the cell membrane were developed. Those polymers have good biocompatibility, and inhibit the adhesion and activation of blood cells, thus minimises blood coagulation when contacts blood [17,19,90]. Feasibility of introducing redox property to phospholipid polymers was investigated.…”
Section: Sem Afmmentioning
confidence: 99%